2018
DOI: 10.1002/pc.24715
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of a composite coating to improve the environmental adaptability of combustible cartridges

Abstract: A combustible cartridge is a kind of porous composite material. It absorbs moisture easily, thus affecting its combustion performance. Usually, storage and protection methods of a combustible cartridge are based on multilayer coatings. However, increasing the number of coatings layers makes the coating process more complex and expensive. In this article, nano‐size titanium dioxide (TiO2) particles were grafted with poly (trifluoroethyl methacrylate). The fluorine‐containing nanocomposite material was used with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Once exposed to a humid environment, the NC‐3C with a cracked coating will be internally wetted and eroded by moisture significantly. In our previous works [1–3], it was also confirmed that the microcracks in the waterproof coating would increase the moisture sensitivity of the coated NC‐3C and were one of the nonnegligible factors inducing the growth of water absorption and the deterioration of environmental adaptability. Besides, the microcracks generated in the waterproof coatings are difficult to monitor.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Once exposed to a humid environment, the NC‐3C with a cracked coating will be internally wetted and eroded by moisture significantly. In our previous works [1–3], it was also confirmed that the microcracks in the waterproof coating would increase the moisture sensitivity of the coated NC‐3C and were one of the nonnegligible factors inducing the growth of water absorption and the deterioration of environmental adaptability. Besides, the microcracks generated in the waterproof coatings are difficult to monitor.…”
Section: Introductionmentioning
confidence: 70%
“…In recent years, many efforts have been made in the development of waterproof coatings for NC-3Cs. For example, functional nitrocellulose varnish coatings [1], organic-inorganic composite coatings [3], and modified silicone resin coatings [2] were successively developed to ameliorate the waterproof performance of NC-3Cs, and the NC-3Cs coated by the abovementioned coatings all exhibited a low water absorption of 0.2 % ~1.0 % in 3.5 wt% NaCl solution after 6 h or more. It can be summarized from the previous studies that endowing the NC-3C substrates with waterproof coatings is an effective design strategy to protect NC-3Cs from moisture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have explored several methods of overcoming this problem, such as adjusting the curing parameters, optimizing the cross-linking system, finding a suitable composite adhesive system, and adding reinforcing materials, etc. [ 9 , 12 , 13 , 14 , 15 , 16 ]. In this work, TDI was used as a curing agent, and glycerol was used as an adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…Our group had conducted some relevant experimental researches extensively. Chen et al [9] grafted poly (trifluoroethyl methacrylate) onto the surface of nanoscale titanium dioxide and mixed it with nitrocellulose varnish to form a coating solution. The prepared multi-functional coating solution was sprayed on the surface of the combustible cartridge case.…”
Section: Introductionmentioning
confidence: 99%